Parallel Grounding Effects on Transformer Resistance and Distribution Substation Reliability - Rizki Maulana; Taryo Taryo (Jurnal Ilmiah Telsinas, 2026)
The grounding system is an essential component of power installations that provides a low-impedance path for fault currents to flow safely into the earth, thereby protecting personnel and equipment from hazards associated with touch and step voltages. Excessive grounding resistance can reduce the effectiveness of protection systems and increase the risk of disturbances and equipment damage. This study aims to analyse the effect of adding a parallel grounding electrode on the grounding resistance of a 250 kVA distribution transformer at the Customer Service Unit of PT PLN (Persero) Cirebon Kota. The research was conducted through field measurements using a Duoyi DY4 100 Digital Earth Tester and the fall-of-potential (three-point) method. Measurements were performed using a single grounding electrode, followed by the installation of an electrode connected in parallel. Measurements were then conducted under the same conditions to evaluate changes in grounding resistance. The data were analysed by comparing resistance values before and after parallelisation based on PUIL 2011, using a grounding resistance criterion of less than or equal to 5 ohms. The results show that grounding resistance decreased from 2.90 ohms to 0.85 ohms, representing a 70.8 percent reduction. This result demonstrates that parallel grounding reduces resistance and improves the safety and reliability of the transformer grounding system.